Social Conflict in the Novel " Dua Barista " By Najhaty Sharma, a Sociology of Literature Approach - Imron Hamdani; Dyah Werdiningsih; Moh Badrih (EDUTEC : Journal of Education And Technology, 2024)
This study aims to describe the forms of social conflict found in the novel "Dua Barista" by Najhaty Sharma, including: (1) interpersonal social conflict, (2) social class conflict, and (3) social group conflict. The research employs a qualitative approach with descriptive analysis. Data collection techniques used in this study include observation, reading, and note-taking. Data validity was verified using triangulation techniques, including source, method, investigator, and theory triangulation. The data sources consist of primary and secondary data. Data analysis techniques involve data reduction, data presentation, and conclusion drawing or verification. The findings of this study reveal that interpersonal social conflicts are manifested as overthinking, social class conflicts are related to social status, and social group conflicts involve disputes. These conflicts arise due to differences in beliefs and interests. This research is expected to complement previous studies on social conflict in literary works and serve as a reference for other researchers interested in literary sociology.